Enhancing Women-led Community-Based Breeding Programs (CBBPs) in Ethiopia - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Community-based breeding program (CBBP) is a genetic improvement program based on the local stock, local experiences and scientific methods of genetics. CBBP is a participatory genetic improvement program that considers informal and community-driven community-based organizations (CBOs). CBBP was initiated in 2009, and over 150 CBBP villages are functional, with considerable success, in Ethiopia through the engagement of research centers, universities, agricultural extension, and NGOs. Women are traditionally responsible for caring for sheep and goats, but men usually make decisions and sales. While the original CBBP programs were theoretically open to all genders, we noticed that the involvement of women in these programs was minimal. Therefore, we started intervening through gender-targeted capacity development and transformative-action community conversations. But gender norms run deep, and we found that, in mixed-gender settings, women were unlikely to speak up or show leadership. When you put everyone together, usually, the men dominate. So, to get an idea of women's roles in breeding programs and other value generators, it's always good to consult the women separately. And at some stage, we said, 'why don't we just start a women's CBBP? Hence, we established women CBBPs in a few villages in Ethiopia starting in 2019. In doing so, we created a safe space for women to speak freely, participate in decision-making, and claim leadership and committee positions. Women-led cooperatives are characterized by the following: Women are the drivers of the CBBP cooperatives, the members of the cooperatives are women, the leadership of the cooperatives is women, and any training and communication are made with women. Women are decisionmakers in CBBPs in women-led CBBPs. The small ruminant innovations are channeled through women's groups. Hence, there is a need to establish more women-led CBBP cooperatives to exploit the inherent indigenous knowledge of women and ensure women's empowerment.